The Case of Dutch and Japanese Colonial Political Policies on Islamic Education in Indonesia: Kasus Kebijakan Politik Kolonial Belanda dan Jepang Terhadap Pendidikan Islam di Indonesia - Dikriati Kamalasari; Muhammad Zalnur; Fauza Masyhudi (Indonesian Journal of Innovation Multidisipliner Research, 2024)
During the colonial period, education must have been very difficult to get, because the colonizers who were in power at that time did not want education to reach the indigenous people. The Islamic education system during the Japanese occupation was basically the same as the Islamic education system in the Dutch era, namely in addition to the pesantren education system established by traditional scholars, there was also a classical education system as seen in madrasas. The Dutch have colonized Indonesia for centuries. And during the Dutch colonial period, access to Islamic education was very difficult because Dutch education was more dominant in non-Islamic education. While Japan actually gave relief to Islamic education in Indonesia, it was precisely the waiver from Japan that made Japan withdraw from Indonesia. The research method used in this study is a Literature Study that collects data from various written sources. This research aims to find out the cases of political policies related to Islamic Education in Indonesia during the Dutch and Japanese colonial periods.